143 Rh-Disease Awareness and Prevention (RhAP): Knowledge Assessment of Obstetrical Patients. (29th October 2021) - Woolf, Maya; Nallathamby, Shanthiya; Gnanalingam, Aasha; Sgro, Michael; Berger, Howard; Baker, Jillian
Abstract: Primary Subject area: Maternal-Fetal Medicine Background: Rhesus hemolytic disease of the newborn (RhD) was once the most common and severe form of hemolytic disease of the newborn with outcomes including anemia, jaundice, stillbirth and death. Approximately 15% of Canadian women are Rh-negative, yet RhD is relatively unknown due to prevention by Rh immunoglobulin (RhIG). There is a need to advocate for the ongoing prevention of RhD in high-income countries (HICs) due to low incidence, vaccine hesitancy and misinformation, and in low-income countries (LICs) where lack of access to RhIG contributes to over 350, 000 annual cases worldwide. Objectives: Our present aim is to assess the current state of knowledge of RhD among women in our centre. Design/Methods: Questionnaires were administered to a consecutive sample of pregnant women of all blood types (5-42 weeks gestation) attending an urban Obstetrics Clinic between January - March 2020, and included demographics and self-reporting of current RhD awareness. Results: Of the 586 participants surveyed, 43% did not know their blood type and 16% identified as Rh-negative (Table 1). Sixty-one percent of participants recalled receiving information about their blood type, and only 31% knew their partner's blood type. Only 45% of the Rh-negative subset (Table 2) in their third trimester (or postpartum) knew that they had been given RhIG (routinely offered at 28 weeks gestation). While 84% of Rh-negative women had received information about RhD from various sources (physician, online, etc.), there was a lack of depth in their knowledge with two-thirds having no knowledge of the common sequelae of RhD. The majority of Rh-negative participants expressed interest in contributing to local efforts (58/92), including interest in our advocacy group. Conclusion: As expected, many participants did not know their Rh status, despite routine testing in pregnancy. Many were unaware of the potential sequelae associated with RhD and rationale for its prevention, even in the Rh-negative subgroup. Not all Rh-negative women were aware of having received RhIG, presumably having received it without knowledge or understanding. We are concerned that lack of awareness, especially among Rh-negative women in HICs may lead to increased complacency, RhIG refusal, and missed opportunities for patient self-advocacy. Our questionnaire results provide further impetus to advocate for increased RhD education for the patients and their care providers. Next steps include the creation of a patient-led focus group that aims to improve local and global awareness of RhD to help decrease the burden of this potentially devastating and preventable disorder.